Long Non-coding RNA Expression Profile and Functional Analysis in Children With Acute Fulminant Myocarditis - Qingqing Liu; Yaru Kong; Bo Han; Diandong Jiang; Hailin Jia; Li Zhang (Frontiers Media S.A., 2019)
Long non-coding RNA (lncRNA) has been associated with human diseases. To study the role of lncRNA in the pathogenic mechanism of acute fulminant myocarditis (AFM), we used a microarray to analyze lncRNA and messenger RNA (mRNA) expression in leukocyte samples from AFM patients and normal children. In total, using a 2/0.5-fold change and P < 0.05 as the cutoff criteria, we found that 3,101 lncRNAs and 2,170 mRNAs were differentially expressed in AFM patients. Quantitative real-time polymerase chain reaction (RT-qPCR) analysis was used to verify the microarray data. Eight differentially expressed molecules were randomly selected, including 3 upregulated lncRNAs, 3 downregulated lncRNAs, and 2 upregulated mRNAs. Among them, 7 expression profiles were consistent with the microarray results. Gene Ontology enrichment and Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis were used to investigate the biological functions of these genes. Establishment of a lncRNA-mRNA co-expression network and lncRNA target predication were performed to study the molecular interactions of these molecules. Our study is the first to use microarrays to examine the lncRNA and mRNA expression profiles associated with AFM, and the results indicate that the immune system plays an important role in AFM. These findings may provide a new perspective for the pathogenesis, diagnosis, and therapy of AFM.